Juridical Review of The Court Judge's Decision on The Divorce Lawsuit Is Unacceptable : Case Decision Number. 393.Pdt.G/2024/Pn.Mdn - Silitonga, Hartati; Nababan, Roida (Manunggal Halim Jaya, 2024)
This research aims to carry out an in-depth analysis of the basis of the Juridical Analysis of the Court Judge's Decision in Case Study No.393/Pdt.G/2024/PN Mdn In an Unacceptable Divorce Suit, it can be seen from the legal side in the field of civil procedural law. This description examines specific legal fields with legal aspects, which are the consequences of the law and juridical aspects of the basic legal considerations. Based on the decision of the Special Class I-A Medan Court Judge, divorce cannot be accepted, which contains absolute requirements for the steps for carrying out a divorce for a member of the Republic of Indonesia Police. The research method is related to a reasonably in-depth analysis of legal explanations and case studies. This research provides a comprehensive understanding of the legal process of divorce, especially regarding the judge's considerations and their impact on both parties involved.